Report of proceedings at the forty-ninth annual Trades union congress : held in the Palace hall, Blackpool, on september 3rd to 8th, 1917 - Trades union congress (49 ; 1917 ; Blackpool)
Published by authority of the Congress and the Parliamentary committee